2009
DOI: 10.1007/s10499-009-9272-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of hatchery-bred giant clams (Tridacna gigas) in an ocean nursery in Sagay Marine Reserve, Philippines

Abstract: To restore the diminishing population of the giant clam Tridacna gigas in Sagay Marine Reserve (SMR), Negros Occidental, central Philippines, two size classes [8-and 10-cm shell length (SL)] of hatchery-bred T. gigas were reared in an adjacent ocean nursery for restocking to Carbin Reef later upon reaching grow-out size of C20 cm SL. Growth rates did not significantly differ for both sizes and were on average 0.67 cm month -1 . However, survival after 382 days of rearing T. gigas was significantly higher in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recent studies addressing the role that incrusting coralline algae may play in the settlement of larval Tridacna revealed that it may attract larvae but does not promote settlement in Tridacna squamosa (Neo et al 2009). Another study by Lebata‐Ramos et al (2010) confirmed the potential of using giant clams produced in captivity for grow‐out in ocean nurseries. However, this approach is unlikely to ever be implemented in European waters (or other places outside the natural distribution of giant clams) to supply the marine aquarium trade.…”
Section: Marine Ornamental Invertebratesmentioning
confidence: 85%
“…Recent studies addressing the role that incrusting coralline algae may play in the settlement of larval Tridacna revealed that it may attract larvae but does not promote settlement in Tridacna squamosa (Neo et al 2009). Another study by Lebata‐Ramos et al (2010) confirmed the potential of using giant clams produced in captivity for grow‐out in ocean nurseries. However, this approach is unlikely to ever be implemented in European waters (or other places outside the natural distribution of giant clams) to supply the marine aquarium trade.…”
Section: Marine Ornamental Invertebratesmentioning
confidence: 85%
“…While there is no published information on the long term growth of restocked giant clams in the Philippines (Lebata-Ramos et al 2010), the use of von Bertalanffy growth formula is the simplest possible way to estimate the ages of live T. gigas and its empty shell. The use of other methods such as growth increment is impossible as most of the samples were only solicited and obtained from the KIs.…”
Section: Age Estimation and Sizes Of Empty Shells And Live T Gigasmentioning
confidence: 99%
“…In the Philippines, giant clams are harvested for both meats and shells (Gomez and Mingoa-Licuanan 2006;Lebata-Ramos et al 2010;Miguelmies and Sumida 2012;Wabnitz et al 2003), but the shells have the greatest economic importance (Juinio et al 1987) especially for international trade (Lucas 1994). The Bureau of Fisheries and Aquatic Resources reported an export of about 243 to 11,930 tons of giant FULL PAPER clams between 1976clams between and 1980clams between (BFAR 1980; however, the volume of trade sharply declined at about 39 to 66 tons due to unregulated harvest (Wells 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The reef flat, approx. 20 ha, is exposed during low tide when the water level goes beyond 0.3 m depth above chart datum (Lebata-Ramos et al, 2010).…”
Section: Study Sitementioning
confidence: 99%